Major Factors of Recidivism among Inmates of Correctional Facilities in Kano State, Nigeria - Abubakar, B.; YA’U, U. H. (Journal of Research in Adult and Continuing Education, 2025)
The paper investigates  the causes and implications of recidivism in Kano State, Nigeria with a view to further broaden the outlook of social welfare educator’s contribution towards promoting the welfare of the inmates to prevent massive recidivism. The present nature of the facilities are punitive in nature not correctional.  As such, this has led to high recidivism among the inmates. Instead of acquiring knowledge and skills that would make them independent, their stay leads them to getting trained by high risk criminals worsening their situation. The paper presents the various factors that lead to recidivism and the ways to prevent recidivism among the inmates in Kano State. Finally, the paper offers some suggestions which include the following: There is needs for community members to note that crime can occur at any time in the community, it is good for people to be vigilant always to prevent occurrences of criminal offences. There is needs for community members to note that inmates are part of the community and they will eventually come back to the community after serving their jail time. Therefore, there is need to show them concern and care. The Correctional officers should try their best to teach the inmates some skills that would help them to become more functional after their release.
Keywords: Factors; Recidivism; Inmates; Correctional; Facilities